Evaluasi Pertumbuhan Uji Provenans Eucalyptus urophylla S.T. Blake Umur 20 Tahun di Lad Krating, Chachoengsao, Thailand) - Indi Hendraswari; Suree Bhumibhamon (Fakultas Kehutanan Universitas Gadjah Mada, 2009)
Evaluation of Provenance Trial of Eucalyptus urophylla S.T. Blake Growth Age 20-Year-old in Lad Krating , Chachoengsao Province, ThailandGrowth characteristics of a wide range of provenance trial of Eucalyptus urophylla established at Lad Krating Plantation, Chachoengsao Province were assessed at 20 years of age. The trial was established to ascertain the extent of variation within the species, identify promising sources for the immediate seed supply and provide information on superior sources for selection. The trial consisted of 18 provenances representing six islands in Indonesia, viz. Flores, Lomblen, Pantar, Alor, Wetar, and Timor. Results from the present study indicated that there were significant differences in survival, tree height, clear bole, diameter at 10 cm above ground level (D10), and diameter at breast height (Dbh) among provenances. Meanwhile, the difference in crown diameter among provenances was insignificant. The present results recommended 6 provenances, viz. Mt. Lewotobi (Flores), Mt. Wasbilla (Pantar), Mt. Kerbau (Lomblen), Mt. Lewerok (Flores), Ampui (Alor), and Mt. Lakaan (Timor) as the best performing provenances for the next selection process and the most promising seed sources to be used in increasing the plantation productivity at Lad Krating.